Formation Of Effective Leadership Communication: A Critical Analysis - Gulmira Meirbekova, Zhanat Burayeva, Moldir Sultanmurat, Usenbek Rakhmet, Parida Iskakova, (Opción, 2019)
On the basis of the study of previous work done by many authors in the past decade, the author has made an attempt to find how leadership is affected by communication. As a result, verbal aggressiveness had a strong negative correlation with human-oriented leadership and a medium-sized negative one with charismatic leadership, but a small (but not significant) positive correlation with task-oriented leadership. In conclusion, different leadership styles also have an impact on communication. As different communication styles have an impact on leadership similarly different leadership also influences communication.